IMPLEMENTASI PASAL 9 AYAT 1 HURUF A UU NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN TERKAIT LARANGAN MENAWARKAN DAN/ATAU MENGIKLANKAN BARANG SECARA TIDAK BENAR SEOLAH BARANG TERSEBUT MEMILIKI POTONGAN HARGA DI KOTA SINGARAJA - Komang Meru Awatara Putra Dinata; ardhya, si ngurah; landrawan, i wayan (Universitas Pendidikan Ganesha, 2025)
The purpose of this study is to determine and analyze the implementation of the provisions of Article 9 Paragraph 1 Letter a of Law No. 8 of 1999 concerning Consumer Protection and to determine the legal consequences for business actors who offer goods incorrectly as if the goods have a discount. The type of research used is empirical legal research with a descriptive research nature. The location of this research was conducted in Singaraja City. The data collection technique used was by means of document study, observation and interview. The sampling technique used was the Non Probability Sampling technique and the determination of the subjects used the Purposive Sampling technique. The data processing and analysis techniques were qualitative. The results of the study indicate that the provisions of Article 9 Paragraph 1 Letter a of the Consumer Protection Law have not been implemented properly. This is reflected in the fact that there are still business actors who offer goods incorrectly as if the goods have a discount. The legal consequences for business actors who offer goods as if there is a discount, namely based on Article 62 Paragraph 1 of the Consumer Protection Law, can be subject to criminal sanctions in the form of imprisonment for a maximum of 5 (five) years and/or a maximum fine of IDR 2,000,000,000.00 (two billion rupiah). If the offer of goods that appear to include a discount is made in electronic media, then based on Article 45a Paragraph 1 of the UUITE, the business actor can be sentenced to a maximum of 6 (six) years and/or a maximum fine of IDR 1,000,000,000.00 (one billion rupiah).